2022
DOI: 10.1089/heq.2021.0179
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity, Financial Hardship, and Mental Health Among Multiple Asian American Ethnic Groups: Findings from the 2020 COVID-19 Household Impact Survey

Abstract: Background: The COVID-19 pandemic has adversely impacted the financial and mental well-being of U.S. adults, however, Asian American (AA)-specific data are lacking, particularly disaggregated by AA ethnicity. Our objective was to evaluate food insecurity (FI), financial hardship, and mental health among disaggregated AA ethnic groups during the COVID-19 pandemic. Methods: We used data from the COVID-19 Household Impact Survey, a sample of 10,760 U.S. adults weighted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, depression and anxiety moods that were caused by COVID-19 spreading among all countries, especially during the first wave, may have influenced food habits since these emotional reactions may have increased craving for comfort eating characterized by assumption of high-fat, high sugar or high-calorie food [ 17 , 22 , 35 ]. Further consideration must be done regarding financial hardship, since the COVID-19 pandemic has led to an economic crisis that influenced food behavior, habits, and food insecurity as indicated by several studies [ 36 – 38 ]. This resulted in a heightened likelihood of unhealthy behaviors and choices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, depression and anxiety moods that were caused by COVID-19 spreading among all countries, especially during the first wave, may have influenced food habits since these emotional reactions may have increased craving for comfort eating characterized by assumption of high-fat, high sugar or high-calorie food [ 17 , 22 , 35 ]. Further consideration must be done regarding financial hardship, since the COVID-19 pandemic has led to an economic crisis that influenced food behavior, habits, and food insecurity as indicated by several studies [ 36 – 38 ]. This resulted in a heightened likelihood of unhealthy behaviors and choices.…”
Section: Discussionmentioning
confidence: 99%
“…The history of individuals racialized as Asian and/or Asian‐Americans in the United States is riddled with residential segregation, workplace discrimination, and food insecurity 14–16 . When integrated with individuals racialized as White, individuals racialized as Asian and/or Asian‐American experience a myriad of interpersonal discrimination, including microaggressions, some leading to more rapid cognitive decline 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The history of individuals racialized as Asian and/or Asian‐Americans in the United States is riddled with residential segregation, workplace discrimination, and food insecurity. 14 , 15 , 16 When integrated with individuals racialized as White, individuals racialized as Asian and/or Asian‐American experience a myriad of interpersonal discrimination, including microaggressions, some leading to more rapid cognitive decline. 17 Most notably, the perceived socioeconomic and integration successes of a few have fueled the construction of the “model minority myth” that erroneously posits that individuals racialized as Asian and/or Asian‐American have achieved socioeconomic and social success, yielding benefits to health and well‐being in the United States.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 8 For instance, one study among adults ages >50 years old found that Black/African American and Latino adults reported more difficulty paying for basic needs and expenses such as food, bills, health care, medical care, and housing during the first year of the pandemic than White adults. 9 Other studies have found that almost half (49.3%) of Asian adults would be unable to pay for an unexpected expense using cash or savings 10 and that 60% of Native Hawaiian/Pacific Islander households experienced a loss of income during the first year of the pandemic. 11 However, additional studies investigating financial hardship during the pandemic among racial/ethnic minority groups, and how financial hardship is experienced (e.g., food insecurity, unmet health care needs) across race–ethnicity is still needed.…”
Section: Introductionmentioning
confidence: 99%